Teaching, research and management at the university: a three world profession (Praxis Educativa, 2012)
During the last years the University has evolved from an institution which focused on the study of different natural and social phenomena to becoming the focus of research. This paper shows part of the results of a research on the effects of social changes in the work and professional life of university teachers. The professional life history has been the strategy chosen to approach the changes in the lives of teachers and researchers. As a result of studying and comparing 24 life histories, there appears a group of different topics which have different meanings for the participants in this research. Their analyses show there is an increase in stress and pressure on teachers who are forced to carry out three completely different activities: teaching, researching and having managerial positions. This text presents the situations teachers have to face in a working context which is becoming more and more demanding.
Keywords: higher education; educational change; professional identity; institutional transformation